2018
DOI: 10.1021/acssynbio.8b00215
|View full text |Cite
|
Sign up to set email alerts
|

Highly Active C8-Acyl-ACP Thioesterase Variant Isolated by a Synthetic Selection Strategy

Abstract: Microbial metabolism is an attractive route for producing medium chain length fatty acids, e.g., octanoic acid, used in the oleochemical industry. One challenge to this strategy is the lack of enzymes that are both highly active in a microbial host and selective toward substrates with desired chain length. Of the many steps in fatty acid biosynthesis, the thioesterase is the most widely used enzyme for controlling chain length. Thioesterases hydrolyze the thioester bond between fatty acids and the acyl-carrier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 41 publications
0
77
0
Order By: Relevance
“…The new thioesterases were based on Cuphea palustris (CpFatB1) (29) and Cuphea avigera pulcherrima (CaFatB3) (30) with varying mutations and truncations (SI Appendix, Fig. S1), two of which were designed according to recent work of Lozada et al (31). Surprisingly, all new thioesterases showed an improvement in 1octanol production compared with Tes3 (15), but the performance varied widely in response to changes in the inducer concentration ( Fig.…”
Section: Thioesterase Selection For 1-octanol Production and Growth Andmentioning
confidence: 99%
See 1 more Smart Citation
“…The new thioesterases were based on Cuphea palustris (CpFatB1) (29) and Cuphea avigera pulcherrima (CaFatB3) (30) with varying mutations and truncations (SI Appendix, Fig. S1), two of which were designed according to recent work of Lozada et al (31). Surprisingly, all new thioesterases showed an improvement in 1octanol production compared with Tes3 (15), but the performance varied widely in response to changes in the inducer concentration ( Fig.…”
Section: Thioesterase Selection For 1-octanol Production and Growth Andmentioning
confidence: 99%
“…With these improvements, the internally produced 1-octanol now exceeded the titer (0.75 mM) at which the underivatized product affected the growth of the strain in the absence of solvent overlay. Lozada et al (31) reported that 'CpFatB1-4 was most effective when the expression level was low, as the strain expressing it showed a growth defect at higher expression levels. This was also observed in our study (SI Appendix, Fig.…”
Section: Thioesterase Selection For 1-octanol Production and Growth Andmentioning
confidence: 99%
“…The substrate specificity of FATs often determines the composition of oils. Thus, many plant FATs have been isolated and remolded to produce oleochemicals with desired chain lengths (Lozada et al 2018). Peanut is an important oil crop (with seed oil content up to 50%), and its genome possesses 21 FATs, which are far more than any other species ( Supplemental Tables S1, S3).…”
Section: Discussionmentioning
confidence: 99%
“…The best design exhibited a 27‐fold improvement in NADH‐dependent activity. Other successes from the same group include, OptGraft for grafting a binding site from one protein into another protein scaffold, rational design to obtain 200‐fold higher D‐hydantoinase activity in Bacillus stearothermophilus using just two amino acid changes, OptZyme for redesigning enzymes by improving binding to a transition state analogue instead of the substrate as it correlates with greater turnover, IPRO Suite of programs for fully‐automated protein redesign, and altering substrate specificity of thioesterase enzyme from long‐chain fatty acyl ACP to medium‐chain ones …”
Section: Successesmentioning
confidence: 99%
“…Recent trends in directed evolution has seen attempts and successes at improving proteins with the biological proviso of still being relevant to the metabolic pathways they belong to, thus creating novel whole cell chemical factories for synthesis of value‐added chemicals . More recently, biochemists have aimed at dialing in novel functionalities in enzymatic proteins which are not seen in nature .…”
Section: Introductionmentioning
confidence: 99%